Diversity of specific indicators of walnut fruits during selection using various methods - Yu. I. Sukhorukikh; S. G. Biganova (Новые технологии)
Walnut (Juglans regia L.) is a particularly valuable plant for humans. This is due to its multifaceted beneficial properties and qualities as a food, medicinal, technical, recreational and environmental tree species. The main goal of nut breeding is to obtain high-quality fruits. In the Russian Federation for the selection of individuals that provide such products, two methods are mainly used: method 1 – «Program and method for breeding walnuts» (Sukhorukikh et al., 2007) and method 2 – «Program and method for the study of fruit, berry and nut crops» (1999). The purpose of the study is to study the diversity of promising forms of walnut identified on the basis of methods 1 and 2 in terms of taste, kernel extractability and the overall score of the breeding value (quality) of the fruit. Other characteristics assessed identically or similarly are not considered. The object of the research was the literature data of the authors assessing the quality of nuts using methods 1, 2. For statistical processing, the Stadia 8.0/prof. program was used, and Microsoft Excel was used for graphical construction. Diversity was assessed using coefficients of variation and indices of distributed rank diversity (IRRR) based on known methods. It was established that the coefficients of variation of the studied indicators, assessed using various methods, did not have a significant statistical difference, and the selection gradations of taste and kernel extractability were equally distributed. When assessed using method 1, the statistical distribution of the total score of the selection value of fruits had a normal distribution, when using method 2 it differed from normal. When assessing diversity using IRRR values, method 1, compared to method 2, turned out to be more sensitive and provided greater diversity of the allocated gene pool in terms of the overall score of the breeding value of walnut fruits. The results can be used in walnut breeding.